Assessment of Catalytic Properties in Aqueous and Media of Aspergillus Niger Lipase Immobilized on Supports Vitreous - A. Melo; E. Mauricio; A.M. Salgado; F.L. Pessoa; M. Damaso; S. Couri (Chemical Engineering Transactions, 2011)
Abstract preview not available - see full-text PDF article.